2019
DOI: 10.1371/journal.pone.0211643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photobiomodulation and exercise on early remodeling of the Achilles tendon in streptozotocin-induced diabetic rats

Abstract: The aim of this study was to compare the treatment effects of laser photobiomodulation (LPBM) therapy and aerobic exercise on the biomechanical properties, tissue morphology and the expression of tendon matrix molecules during early remodeling of Achilles tendon (AT) injury in diabetic rats. Animals were randomly assigned to five groups: injured non diabetic (I, n = 15), injured diabetic (ID, n = 15), injured diabetic plus LPBM (IDL, n = 16), injured diabetic plus aerobic exercise (IDE, n = 16) and injured dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…The diabetic patellar tendon had significantly decreased stiffness with a reduced Young’s modulus[ 15 ]. However, Thomas et al [ 35 ] showed that hyperglycemia did not alter mechanics (stiffness and modulus) at either insertion site or mid-substance of the supraspinatus tendon, while some studies showed no significant changes in biomechanical properties between diabetic and nondiabetic tendons[ 12 , 36 ].…”
Section: Changes In Biomechanical Properties In Diabetic Tendinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The diabetic patellar tendon had significantly decreased stiffness with a reduced Young’s modulus[ 15 ]. However, Thomas et al [ 35 ] showed that hyperglycemia did not alter mechanics (stiffness and modulus) at either insertion site or mid-substance of the supraspinatus tendon, while some studies showed no significant changes in biomechanical properties between diabetic and nondiabetic tendons[ 12 , 36 ].…”
Section: Changes In Biomechanical Properties In Diabetic Tendinopathymentioning
confidence: 99%
“…The repair and regenerative capacity of diabetic tendons is compromised during the healing process after injury. Fibroblast proliferation[ 43 , 44 ], vascularity[ 21 , 44 , 45 ], and collagen levels[ 36 , 44 ] were reduced in injured diabetic tendons during healing. Egemen et al [ 43 ] showed that although similar collagen deposition and vessel proliferation were observed in both injured diabetic and nondiabetic tendons during healing, lymphocyte infiltration and osteochondroid metaplasia of some tenocytes were observed in the injured diabetic tendons.…”
Section: Histopathological Alterations In Diabetic Tendinopathymentioning
confidence: 99%
“…Os dados glicêmicos dos animais estão representados na Tabela 1. Conforme mostra a tabela os animais permaneceram hiperglicêmicos até o fim do período experimental assim como nos demais estudos com o mesmo modelo experimental (DE OLIVEIRA et al, 2019). O grupo DAC teve a glicemia reduzida significativamente versus o grupo D, mostrando o potencial hipoglicemiante desta planta (LEE et al, 2013).…”
Section: Resultsunclassified
“…Disorders affecting the musculoskeletal system have also been shown to be associated with changes in MMPs since tendon, bone, articular cartilage, ligament, and other components are ECM-rich organs 18 . The connective tissue predominating in such structures constitutes mainly of fibrillar collagen (type I, II, and III) as they have load-bearing roles 10,16,24 . Hence, tightly regulated ECM degradation is required from MMPs, especially the collagenases.…”
Section: Joint and Ligamentsmentioning
confidence: 99%
“…Regulation of MMPs must be notably tight, otherwise either their inhibition or overexpression can easily lead to breakdown of tissue homeostasis 13 . Structural alterations associated with MMP dysregulation manifest as, among others, impaired healing 14 , organ fibrosis, 15 and ECM disorganization 16 . Interestingly, MMPs have been shown to be responsive to HBO 2 , making them a key target for investigation 3,6 .…”
Section: Introductionmentioning
confidence: 99%